Fairness as a source of hysteresis in employment and relative wages - Peter Skott (University of Massachusetts, Department of Economics, 2004)
This paper analyses the influence of norms of fairness on wage formation. Fairness is defined by `real-wage' and `relative-wage' norms that relate wage offers to workers' own current wage and to the wages of other groups of workers, and, to avoid shirking, firms pay fair wages. The wage norms change endogenously, and the result is hysteresis with respect to both employment and the distribution of wages. An extension of the model that allows `induced overeducation' may help explain trends in wage inequality.
Keywords: 330; Wage norms; fairness; hysteresis; overeducation; wage inequality; unemployment